Financial Distress Likelihood and Social Performance of Listed Firms. The Effect of Mandatory CSR Policy. - Oware, Kofi Mintah, Mallikarjunappa T. (International Journal of Advanced Science and Technology, 2020)
Motivated by institutional theory, this study investigates the effect of mandatory corporate social responsibility policy on the financial distress likelihood and social performance (activity and disclosure) of listed firms. The panel models applied on 800 firm-year observations for the period 2010 to 2019 and used the Indian stock market as a testing ground. The findings show that an increase in social performance activity more than likely causes a reduction in the likelihood of financial distress and are significant in extraction industries. Also, financial distress firms do not cause an increase in social performance activity of listed firms. The findings also show that the introduction of the mandatory CSR policy does not cause a financial distress likelihood of listed firms. Also, the study shows that the introduction and implementation of mandatory CSR policy cause an increase in the practice of CSR and ultimately increases the social performance disclosure of listed firms and is significant in the service industries. Lastly, the institutional theory is relevant in the explanation of the relationship of the study. The implication from the study shows that the mandatory CSR policy introduction causes firms to increase social performance disclosure in its sustainability reporting to shareholders. There are no bi-directional studies that examine how social performance activity culminating from mandatory policy, worsens or improves financial distress likelihood of listed firms. Also, the significance from different industries perspective in mandatory CSR policy and social performance disclosure contributes novelty to CSR studies.